Antisemitism as political theology in Greece and its impact on Greek Jewry, 1967–1979. Issue 2 (3rd April 2017) - Blümel, Tobias
Abstract: Greece, especially after 1945, remains a terra incognita of antisemitism research. This is not only a scholarly problem but also affects contemporary Greek judicature, which in 2009 and 2010 – during the controversial trial against Konstantinos A. Plevris, the so-called intellectual head of contemporary Greek Nazism – determined Holocaust denial, ariosophic fantasies of racial superiority and the public demand for the extinction of European Jewry to fall under the definition of 'freedom of the arts, science and research.' Some of the central historical sources the Greek courts accepted to be allegedly authentic enough to scientifically prove the 'Jew-Zionists' [evraiosionistes, T.B.] aspirations to world power' were excerpts from the book of a fanatic nineteenth-century blood-libel author in Russia along with the internationally known antisemitic forgery, The Protocols of the Elders of Zion . The following article will argue that the origin of antisemitism in Greece is a phenomenon at the intersection of pre-Enlightenment and modernity, namely founded upon an ideological framework of nation, religion and race.